Independence of internal audit in public sector organizations a case of Chitungwiza municipality - Mange, Tapiwa (Midlands State University, 2014)
This paper has focused much on the independence and performance of internal audit in public sector organizations. The research objectives of this project are to examine the relationship between internal audit and the management in all council operations, to assess effectiveness of internal audit controls both existing and proposed functions, to examine challenges faced by Chitungwiza municipality in upholding independence of internal audit and accountability including management’s behaviour, to determine types of internal audit and their subsequent efficient methods at the council, to investigate how size and resourcing of internal audit affect objectivity and efficiency and to recommend strategies of establishing an effective and independent internal audit. In the literature review methods of measuring the effectiveness of internal audit activity were discussed in detail. This study provides empirical evidence as to the main factors influencing internal audit independence. Internal audit effectiveness can be only enhanced through its independence; there are various factors that contribute to autonomy of internal audit in public sector organizations. These factors are namely competence of internal audit, the size of the internal audit department, the relationship between internal and external auditors, management support for internal audit and the independence of the internal audit department. The results suggested that management should support the internal audit function and promote internal audit autonomy from political interference. This would bring effectiveness of both the internal audit function and management. In this context, literature was also reviewed whereby different views were given towards autonym of internal audit in public sector. Internal audit was defined, forms of internal audit that internal auditors comply with such as Financial audit, Risk management and system controls, Advisory and investigative service and Performance audit. The researcher used research methodology that was mutually blended with both qualitative and quantitative research designs. The population for this research is 497 people constituting general employees (top management, lower level internal audit employees, councillors and the workers union members. The sample population is 50 and it constitutes 25 from the general lower level employees, 7 from the top management, 10 from councillors, 4 from internal audit employees and 4 from the workers committee. The research tools used were interviews and questionnaires which had both open-ended and closed questions. Sampling techniques used are purposive, stratified and simple random sampling. Data was gathered from this targeted population through the use of face to face interviews and questionnaires. The researcher presented data which reveals different types and forms of internal audit. Moreover, challenges that are faced by Chitungwiza municipality in enhancing independent internal audit were unfolded by respondents. Respondents also cited that independence of internal audit has different benefits such as effectiveness, accountability, transparency and efficiency. It was concluded that internal audit should be established outside the organisation. Internal audit management should be given motivational grades and salaries for them to be committed. In addition, internal audit should report to an outside separate entity and it has been recommended that there should be qualified workforce in internal audit department and they should be given access to every aspect of organizational financial and operational transactions